1987
DOI: 10.1007/bf02555700
|View full text |Cite
|
Sign up to set email alerts
|

Effect of body weight on osteopenia in ovariectomized rats

Abstract: Bilateral ovariectomies or sham surgeries were performed in female Sprague Dawley rats that were 78 days of age and weighed an average of 210 g. Food was available ad libitum to the control rats and to a group of ovariectomized rats (obese OVX). The food consumption of a second group of ovariectomized rats (weight-matched OVX) was restricted to match their body weights to those of the control rats. All rats were sacrificed at 14 weeks postovariectomy. Radioimmunoassay of terminal serum estradiol confirmed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
95
5
6

Year Published

1993
1993
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 236 publications
(121 citation statements)
references
References 15 publications
14
95
5
6
Order By: Relevance
“…However, it could be suggested that food intake decreased during the first days after osteotomy and then rose recovering to its level (from 8 to 15 g/rat per day in average respectively). This assumption is supported by other results showing that food intake of the intact and Ovx Sprague-Dawley rats of 3 to 6 months of age ranged from 16 to 18 g/rat per day (Wronski et al 1987, Vortherms 2006.…”
Section: Animal Modelsupporting
confidence: 64%
“…However, it could be suggested that food intake decreased during the first days after osteotomy and then rose recovering to its level (from 8 to 15 g/rat per day in average respectively). This assumption is supported by other results showing that food intake of the intact and Ovx Sprague-Dawley rats of 3 to 6 months of age ranged from 16 to 18 g/rat per day (Wronski et al 1987, Vortherms 2006.…”
Section: Animal Modelsupporting
confidence: 64%
“…Much evidence has shown that BMD decreases with increasing age in men, and is accompanied by decreasing sex hormones, but more moderately than in post-menopausal women [5,10,17,18,23,24]. According to previous studies, the high BMD or calcium content of the first and fourth lumbar vertebrae, femur, and tibia coincided with a high testosterone level at the age of 12 months in male Wistar rats [11,14,17].…”
Section: Discussionmentioning
confidence: 97%
“…This is because the rate of increase was within 10 percent of the preorchidectomy rate and because all the dogs used in this study were kept in cages and had restricted exercise during the experimental period. Indeed, Wronski et al [21] have shown that body weight did not influence the decrease in bone volume in ovariectomized rats. Although our findings have demonstrated that the loss of sex hormones produced by orchidectomy in male dogs successfully changed both the serum biochemical and histomorphometric parameters, which suggests the occurrence of osteoporosis, the histomorphometric and serum biochemical parameters did not always change in ovariectomized dogs [14,18].…”
Section: Discussionmentioning
confidence: 97%